Hierarchically porous materials: synthesis strategies and structure design - Yang, Xiao-Yu; Chen, Li-Hua; Li, Yu; Rooke, Joanna Claire; Sanchez, Clément; Su, Bao-Lian (Chemical Society reviews, 2017)
Owing to their immense potential in energy conversion and storage, catalysis, photocatalysis, adsorption, separation and life science applications, significant interest has been devoted to the design and synthesis of hierarchically porous materials. The hierarchy of materials on porosity, structural, morphological, and component levels is key for high performance in all kinds of applications. Synthesis and applications of hierarchically structured porous materials have become a rapidly evolving field of current interest. A large series of synthesis methods have been developed. This review addresses recent advances made in studies of this topic. After identifying the advantages and problems of natural hierarchically porous materials, synthetic hierarchically porous materials are presented. The synthesis strategies used to prepare hierarchically porous materials are first introduced and the features of synthesis and the resulting structures are presented using a series of examples. These involve templating methods (surfactant templating, nanocasting, macroporous polymer templating, colloidal crystal templating and bioinspired process, i.e. biotemplating), conventional techniques (supercritical fluids, emulsion, freeze-drying, breath figures, selective leaching, phase separation, zeolitization process, and replication) and basic methods (sol-gel controlling and post-treatment), as well as self-formation phenomenon of porous hierarchy. A series of detailed examples are given to show methods for the synthesis of hierarchically porous structures with various chemical compositions (dual porosities: micro-micropores, micro-mesopores, micro-macropores, meso-mesopores, meso-macropores, multiple porosities: micro-meso-macropores and meso-meso-macropores). We hope that this review will be helpful for those entering the field and also for those in the field who want quick access to helpful reference information about the synthesis of new hierarchically porous materials and methods to control their structure and morphology.